Equation of state for β-stable hot nuclear matter - Moustakidis, Ch. C. (HNPS Advances in Nuclear Physics, 2020)
We provide an equation of state for hot nuclear matter in β-equilibrium by applying a momentum-dependent effective interaction. We focus on the study of the equation of state of high-density and high-temperature nuclear matter, containing leptons (electrons and muons) under the chemical equilibrium condition in which neutrinos have left the system. Special attention is dedicated to the study of the contribution of the components of β-stable nuclear matter to the entropy per particle, a quantity of great interest for the study of structure and collapse of supernova.